Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 2 - Real Numbers - Chapters 1-2 Cumulative Review Problem Set - Page 91: 14



Work Step by Step

The algebraic expression will be evaluated by substituting the values of $x=-2$ and $y=-4$ into the expression: $-4x^{2}y-2xy^{2}+xy$ =$-4(-2)^{2}(-4)-2(-2)(-4)^{2}+(-2)(-4)$ =$-4(4)(-4)-2(-2)(16)+(8)$ =$-4(-16)-2(-32)+(8)$ =$64+64+8$ =$136$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.